Ghana : Ghana-Fourth and Fifth Reviews Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Nonobservance of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2006)
Ghana's macroeconomic performance has continued to improve, and the program's objectives are being met. Progress has also been made toward achieving the Millennium Development Goals. Public expenditure and financial management has shown improvement. The medium-term outlook appears favorable and the economy is poised for acceleration in growth. Recent petroleum price adjustments have delayed the disinflation process. The transparency of exchange rate policy is essential. Executive Directors agree with the government's determination to lay a strong foundation for the private sector to lead growth.